AN ANALYTICAL STUDY OF BEHAVIORIST, COGNITIVIST, AND CONSTRUCTIVIST PARADIGMS IN ENGLISH LANGUAGE PEDAGOGY - Karimova Nigina Sunnatillo qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
This study provides a comprehensive analytical examination of the three major theoretical paradigms behaviorism, cognitivism, and constructivism—and their implications for English language pedagogy. The research explores how each paradigm conceptualizes the process of language learning and the role of the teacher and learner within instructional settings. Behaviorism emphasizes habit formation through repetition, reinforcement, and stimulus-response mechanisms, thereby shaping traditional drill-based teaching practices. In contrast, cognitivism focuses on internal mental processes, highlighting the importance of memory, perception, and information processing in acquiring linguistic competence. Constructivism, on the other hand, views learning as an active, socially mediated process in which learners construct knowledge through interaction and experience.